Assessment of Right Ventricular Functions in Patients with Rheumatoid Arthritis by Tissue Doppler Imaging and 2D Speckle-Tracking Echocardiography - Hussein Faiz Sahib; Ali Jaber Al-Mamoori; Hassanain M. Saeed (Medical Journal of Babylon)
Background:Advanced echocardiographic techniques play a crucial role in evaluating right ventricular function and providing valuable information for the management of rheumatoid arthritis (RA)-related cardiovascular complications. Objectives:To investigate early signs of right ventricle dysfunction in patients with RA using tissue Doppler imaging and two- dimensional speckle-tracking echocardiography (GLS). Materials and Methods: This case–control study examined cardiac changes in 50 RA patients compared to 50 healthy controls. Echocardiography and anthropometric measurements were used to assess ejection fraction, ventricle systolic and diastolic function, and myocardial strain. Results:The study examined socio-demographic characteristics and echocardiographic parameters in RA patients (N = 50) compared to controls. RA patients had a mean age of 48.28 ± 11.06 years, with 74.0% females. No significant differences in age, BMI, and body surface area between RA patients and controls. There were no significant mean differences between the two study groups according to ejection fraction. There is a significant difference in right ventricular systolic function (TAPSE, S^ velocity, and MPI) observed in RA patients. There is a significant difference in right ventricular diastolic function (E/A ratio, IVRT) observed in RA patients. Global longitudinal strain (GLS) was also significantly reduced. The treatment strategy (single vs. combination therapy) did not significantly affect echocardiographic parameters. The findings emphasize the importance of monitoring cardiac health in RA patients. RA patients show cardiac function alterations, particularly in right ventricular systolic function (TAPSE, S^, and MPI), right ventricular diastolic function (E/A ratio, IVRT), and global function (GLS). Conclusion:Monitoring cardiovascular health in RA patients is crucial. Treatment regimens (combination or monotherapy) did not significantly affect the measured echocardiographic parameters.